Synthesis and structural determination of [Rh(opo)(CO)(PR3)] complexes (opo− = 2-oxopyridin-1-olate) and in situ isomeric behavior from preliminary kinetic study of iodomethane oxidative addition. Issue 1 (24th January 2021) - Elmakki, Mohammed A. E.; Alexander, Orbett T.; Venter, Gertruida J. S.; Venter, Johan A.; Roodt, Andreas
Abstract: A range of complexes, [Rh(opo)(CO)(PR3 )], with opo − = 2-oxopyridin-1-olate, and [Rh(opo)(CO)2 ] (1 ), [Rh(opo)(CO)(PPh3 )] (2AI /BI ), [Rh(opo)(CO)(PPh2 Cy)] (3AI /BI ), [Rh(opo)(CO)(PPhCy2 )] (4AI /BI ), [Rh(opo) (CO)(PCy3 )] (5AI /BI ), [Rh(opo)(CO)(P( o -Tol)3 )] (6AI /BI ), [Rh(opo)(CO) (P( m -Tol)3 )] (7AI /BI ), [Rh(opo)(CO)(P( p -Tol)3 )] (8AI /BI ), and cis -[Rh(opo)(CO)(CH3 )(I)(PPh3 )] (2AII ), were synthesized and characterized by IR and NMR spectroscopy. Two isomers (A = major, MaI; B = minor, MiI) were observed in ca. 2:1 ratios for complexes 2–8 due to the similar characteristics of the chelating O-donors, yet non-symmetric within the bidentate ligand. Single crystal X-ray diffraction yielded the solid-state structures of the major isomers of 4AI, 5AI, 6AI, and 2AII . Metallophilic interactions were observed between neighboring Rh(I) centers in [Rh(opo)(CO)2 ] (1 ) with an intermolecular Rh···Rh distance of 3.5780(5) Å. These interactions do not occur in the crystal structures of 4AI, 5AI, 6AI, and 2AII, attributed to the steric bulk of the phosphine ligands and the interactions observed in the crystal lattice of these structures. Preliminary iodomethane oxidative addition (OA) to the rhodium(I) complexes [Rh(opo)(CO)(PR3 )] was investigated by IR, NMR, and UV-Vis spectroscopy, yielding corresponding alkyl intermediate species (nAII /BII ) or acyl products (nAIII /BIII ), respectively, for n = 2–8 and PR3 = PPh3 (2 ), PPh2 Cy (3 ), PPhCy2 (4 ), PCy3 (5 ), P( o -Tol)3 (6 ), P( m -Tol)3 (7 ), P( p -Tol)3 (8 ). The rates of OA and assumed subsequent migratory carbonyl insertion (CI) reactions were identical within standard deviations, suggesting the CI to be fast relative to the OA. Moreover, the interconversion between the two isomers A and B seemed to be a slower process, governed by the relative steric strain induced by the tertiary phosphine ligands and not by the rates. Graphical Abstract: